Dispensasi Perkawinan oleh Hakim PA Ponorogo Perspektif Peraturan Mahkamah Agung Nomor 5 Tahun 2019 - M. Akhlis Azamuddin Tifani; Ahmad Junaidi (Journal of Economics, Law, and Humanities, 2023)
The concern in this study is about the judges' decisions, with 96% of decisions that legalize marriage dispensation applications. This fact contradicts the spirit of Supreme Court Regulation Number 5 of 2019, which seeks to minimize the number of underage marriages. Some of these problems become the researchers' anxiety in finding out about several things, including; 1) The paradigm of Ponorogo Religious Court Judges in handling marriage dispensation cases, 2) the effectiveness of the implementation of Supreme Court Regulation Number 5 of 2019 by Ponorogo Religious Court Judges in the case of marriage dispensation.